Implementasi Wazuh Integritas File untuk Perlindungan Keamanan Berdasarkan Aktivitas Log di BTSI UKSW - Bagas Haryanto; Dian W. Chandra (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
Technological developments are now increasingly sophisticated, especially in data security. Data security and File Integrity have an essential role and are one of the main concerns in the corporate environment. Practical steps are needed for a data security system that detects data threats, especially File Integrity within the SWCU BTSI environment. The Wazuh system provides monitoring and detection of File change activity. This feature works because of Real-Real File change activity and log analysis. To maintain system security is to monitor File Integrity, namely ensuring that critical Files are not subject to unauthorized changes by unauthorized parties. Therefore, research was carried out and implementation of File Integrity Wazuh for security protection based on log activity at SWCU BTSI. The results showed that the implementation of the File Integrity Wazuh system can identify security incidents against suspicious activity on a File and is effectively able to provide notifications to administrators against unauthorized activity